Groups with weak maximality condition for nonnilpotent subgroups - Kurdachenko, L. A.; Semko, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
A group $G$ satisfies the weak maximality condition for nonnilpotent subgroups or, shortly, the condition Wmax-(non-nil), if $G$does not possess the infinite ascending chains $\{H_n | n \in N\}$ of nonnilpotent subgroups such that the indexes $|H_{n+i} :\; H_n |$ are infinite for all $n \in N$. In the present paper, we study the structure of hypercentral groups satisfying the weak maximality condition for nonnilpotent subgroups.